2019
DOI: 10.1177/1179556519870520
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus–Associated Oropharyngeal High-Grade Neuroendocrine Carcinoma in an Adolescent: Case Report and Review of Literature

Abstract: Oropharyngeal small cell carcinomas (OPSmCC) are rare with only few case reports and case series published in the literature. More recently, an association of these tumors with human papillomavirus (HPV) infection has been detected. However, unlike oropharyngeal squamous cell carcinomas which have a better outcome when associated with HPV, OPSmCC exhibit an aggressive behavior. In this article, we report a case of tonsillar carcinoma arising in a 14-year-old boy that was associated with HPV infection. The tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A PRISMA diagram outlining the literature search is shown in Figure 1. Fifty full‐text articles published from 1987 to 2020 were ultimately included in this systematic review 4,5,8–12,18–60 . Further details regarding these publications including the Oxford level of evidence can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A PRISMA diagram outlining the literature search is shown in Figure 1. Fifty full‐text articles published from 1987 to 2020 were ultimately included in this systematic review 4,5,8–12,18–60 . Further details regarding these publications including the Oxford level of evidence can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of p16/HPV status for the prediction of treatment response and prognosis in patients with PD NEC is uncertain. The results of p16 IHC and HPV status determination showed that, indeed, most (but not all) p16-positive and HPV-positive cases originated from the oropharynx; however, in contrast to the case for squamous cell carcinoma, the p16 status in PD NEC cannot be used as a surrogate marker of HPV status due to its low specificity [ 38 , 39 , 40 ]. Namely, the frequently seen overexpression of p16 in LC/SC-NEC of the head and neck may also be due to a virus-independent Rb pathway dysregulation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the extent of the disease was not included in the multivariate model which, in several analyses (including ours), has proved to be an important prognostic factor, the results of this study should be interpreted with caution. Furthermore, upon reviewing the literature specifically focused on oropharyngeal PD NEC, Sinno et al found no survival advantage of HPV positivity, although without regard to the stage of disease [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, NEC located in the base of the tongue and tonsils were not included since these sites are considered to be part of the oropharynx. Moreover, Sinno et al [39] have recently reviewed the literature concerning oropharyngeal NEC and our aim was to focus on oral cavity and jawbone cases [39].…”
Section: Discussionmentioning
confidence: 99%